Marginalization of Minority Ethnicities in Ethnic Humor Discourse in Indonesia: A Critical Discourse Analysis - Surahmat, Surahmat; Wijana, I Dewa Putu; Sulistyowati, Sulistyowati (Masyarakat Linguistik Indonesia Universitas Andalas, 2024)
This study aims to explain the role of ethnic humor as a practice of marginalization against minority ethnic groups in Indonesia. The research data consists of 270 instances of ethnic humor sourced from books, websites, and social media. The data were analyzed using Fairclough’s critical discourse analysis approach, which includes three stages: description, interpretation, and explanation. Textual characteristics of ethnic humor were analyzed using SketchEngine, a corpus management and text analysis software developed by Lexical Computing. The findings indicate that ethnic humor can marginalize minority ethnic groups in Indonesia through three mechanisms: (1) negatively representing the targeted ethnic group, (2) constructing unequal social relations, and (3) justifying the behavior of the targeted ethnic group as inferior, strange, or even negative. The ideology embedded in ethnic humor discourse can be traced through patterns of language use, including word choice, sentence structure, and discourse organization. Words, sentence strcuture, and discourse organization are ideological because they contain experiential, relational, and expressive values. The results of this study reveal that ethnic humor, often appreciated for its entertainment value, can marginalize minority ethnic groups in two ways: by restricting their identity and roles. These findings reinforce previous research, such as that conducted by Pérez (2022), which argues that the ideological nature of ethnic humor can be harmful as it reinforces the dominance of majority groups. This finding also reinforce the findings of Mendiburo-Seguel & Ford (2023) which show that ethnic humor can strengthen ethnic prejudice. This situation suggests that ethnic humor should be approached cautiously to avoid negative impacts on Indonesia’s multiethnic society.